Teoria do ruído e fenômenos de interferência quântica em nano estruturas quirais - Barros, Marília Santos Melo de (2018)
This thesis is dedicated to the investigation of the universal properties of the electronic transportation in mesoscopic system. At the theoretical level, we introduce the chiral symmetry in chaotic ballistics cavities creating the so-called chaotic billiards of Dirac. For this exact analytical approach, we initially used the diagrammatic method proposed by Brouwer and Beenakker and we built a generalized theory of the integration on the unitary group. The whole calculation incorporates the effect of the chaos through the use of the theory of random matrices. In particular, we calculated physical observables of transportation, such as, the conductance and the power of the shot’s noise. We presented exact results for the observable of transportation relevant in billiards of Dirac chaotic and, posteriorly, compared to the results of Schrödinger billiards, displaying the concerned peculiarities to the universal classes chiral and the classes of Wigner-Dyson. In this context, we presented the study of the crossover of the orthogonal circular ensemble to the unitary circularensembleandthereasonoftheweaklocalizationcorrectiontothenoisepotentialof the shot and to the conductance of the billiard of Dirac.